Native American place names in Mississippi - Baca, Keith A. (University Press of Mississippi, 2007)
Biloxi. Tunica. Pascagoula. Yazoo. Tishomingo. Yalobusha. Tallahatchie. Itta Bena. Yockanookany. Bogue Chitto. These and hundreds of other place names of Native American origin are scattered across the map of Mississippi. Described by writer Willie Morris as "the mysterious, lost euphonious litany," such colorful names, which were given by the Choctaw, Chickasaw, and other tribes, contribute significantly to the state's sense of place. Yet the general public is largely unaware of exact meanings and tribal roots. Native American Place Names in Mississippi is the first reference book devoted to a subject of interest to residents and visitors alike. From large rivers and towns to tiny creeks and rural communities, Keith A. Baca identifies the most likely meanings of many names with more than one recorded interpretation. He corrects misconceptions that have arisen over the years and translates numerous names for the first time. For the benefit of travelers, he provides the location of each named place. To bring attention to often inconspicuous and unmarked streams he also indicates points where highways cross rivers and creeks with Native American appellations. Sidebars present Native American history, legends, and myths that surround these enigmatic and alluring designations. Formerly an archaeologist with the Mississippi Department of Archives and History, Keith A. Baca is an independent researcher and writer living in Starkville, Mississippi. He is the author of the award-winning Indian Mounds of Mississippi: A Visitor's Guide